Improvement of the Technology of Liquefaction of Cast Iron in an Electric ARC Furnace - Jamshidbek Khasanov; Nodir Turakhodjaev; Shokhista Saidkhodjaeva; Shukhrat Chorshanbiyev (International Journal on Integrated Education, 2022)
This article examines the problems that occur when liquefying cast iron in electric tea furnaces and how to overcome them. With the widespread use of electric tea furnaces in foundries, the search for solutions to its problems is urgent today.